PERANCANGAN APLIKASI PERSEDIAAN BARANG BERBASIS WEB PADA KEDAI RB.CO - Abdul Azis, - (2018)
Kedai RB.CO is a restaurant business, is a very growing business diversity in indonesia today. To survive in this business competition, entrepreneurs not only prioritize the type of food or the price alone, but also need to emphasize the stock of goods, so far still done conventionally in the form of paper sheets that make it difficult in terms of data collection because the more accumulate paper or paper already broken. Difficulties and complexity can be overcome by utilizing the progress of information technology that utilizes WEB-based programs to manage inventory, managers make use of WEB-based perogram, the results of inventory data will be stored in the database to facilitate the data collection, so data items are not easily damaged. Design method to analyze problem using PIECES method, while design model apply UML method